Zaydi Perspective on the Imamate - Saja Hadi Wathiq, Asst. Lecturer (lark, 2026)
This study examines Zaydism as a Shiʿi sect that has maintained its presence and influence throughout Islamic history. It focuses on the intellectual foundations of the sect, particularly concerning the concept of Imamate, a central issue in Islamic thought. The study outlines the origins of Zaydism based on the teachings of Imam Zayd ibn ʿAli ibn al-Husayn (peace be upon them) and highlights their criteria for leadership, including the permissibility of a less virtuous Imam, the requirement of descent from al-Hasan or al-Husayn, and moral and religious qualifications. It also addresses their stance on multiple Imams in distant regions and their rejection of Imam infallibility.
Keywords: Zaydism – Imamate – Shiʿi Sects